FEATURES OF PERSONNEL MONITORING IMPLEMENTATION AT MODERN ENTERPRISES - HELMAN, Valentina; BEXHTER, Lilija; TOBOLKIN, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Businesses related to various niches and industries use employee monitoring to protect themselves from potential risks of data leakage and other external threats. Employee monitoring is a new strategy in today’s business that is central to improving productivity and operational efficiency. The application of scientific methods of monitoring and analyzing the activities of employees in real time allows organizations to achieve a high level of accountability, optimal allocation of resources and making informed management decisions. Such a monitoring system contributes to the rise and development of the enterprise, creating a more productive and motivated work environment. The article examines the peculiarities of the implementation of employee monitoring as an important tool for ensuring the efficient operation of the enterprise, maintaining labor discipline and rational use of resources. Separate forms of monitoring that are used in practice are considered. Attention is focused on the legal aspects of the monitoring process, compliance with the needs of both employers and employees, in particular, taking into account the rights and privacy of the latter. In the modern conditions of business operation and development, employers have an interest in the most efficient use of their staff’s working time. Time control is one way to achieve this. Controlling working hours can be efficient and beneficial for a company, but it can also raise certain ethical and legal issues. It is important that this control is carried out in compliance with all relevant legal requirements and taking into account the rights and interests of employees. Therefore, the employer must develop and implement internal regulatory documents that regulate monitoring procedures, as well as ensure that employees are informed about their rights and obligations in this process. This will avoid conflicts and ensure the legal purity of monitoring, maintaining a balance between the needs of the enterprise and the rights of employees. The choice of personnel monitoring and tracking tools is not limited to technical aspects, but includes the creation of a culture of trust and openness in the relationship between the employer and employees.